Areas of crisis management of operational activities of industrial enterprises in the pandemic Covid-19 - Belikova, O.; Voloshina, O.; Melchenko, V.; Barkova, S. (Економічний вісник Донбасу, 2025)
In the context of a global pandemic, one of the main tasks of enterprise management should be to create an effective anti-crisis management system. The article examines the problem of application of crisis management in the enterprise in a Pandemic, theoretical justification and development of practical recommendations for enterprise management in a crisis. Differences between traditional crises and business destabilization due to the pandemic have been identified. Indicators of support of entrepreneurial activity by state structures of the world are analyzed. It is determined that to prevent the negative impact of factors on operating activities in a crisis, it is advisable to use effective methods, forms of crisis management. The expediency of using the mechanism of anti-crisis management of operational activities of domestic enterprises has been clarified. The necessity of introduction of the system of anti-crisis management at the domestic enterprises for the purpose of maintenance of economic development is substantiated. В умовах глобальної пандемії одним із головних завдань управління підприємством має стати створення ефективної системи антикризового управління. У статті розглядається проблема застосування кризового менеджменту на підприємстві в умовах пандемії, теоретичне обґрунтування та розробка практичних рекомендацій щодо управління підприємством у кризових умовах. Визначено відмінності між традиційними кризами та дестабілізацією бізнесу внаслідок пандемії. Проаналізовано показники підтримки підприємницької діяльності державними структурами світу. Визначено, що для запобігання негативному впливу факторів на операційну діяльність у кризових умовах доцільно використовувати ефективні методи, форми кризового управління. З'ясовано доцільність використання механізму антикризового управління операційною діяльністю вітчизняних підприємств. Обґрунтовано необхідність впровадження системи антикризового управління на вітчизняних підприємствах з метою підтримки економічного розвитку.